Histopathological Evaluation and Analysis of Immunohistochemical Expression of Bcl-2 Oncoprotein in Colorectal Carcinoma - Shilpa Patil; Clement Devadass; Prasanna Badila (Iranian Society of Pathology, 2019)
Background & Objective: Colorectal cancer is the third most prevalent malignancy with high mortality rate, necessitating markers that predict survival and guide the treatment. Previous studies have examined the immunohistochemical expression of Bcl-2, an apoptotic marker, in colorectal carcinoma, but results have been contradictory. To evaluate the histopathological features of colorectal carcinoma, immunohistochemical expression of Bcl-2 must be analyzed to find out statistical association of Bcl-2 expression with certain prognostic factors histopathologic type, grade and TNM staging. Methods: This prospective study was conducted on the colectomy specimens of colorectal carcinoma, over a period of two years. The tumor morphology and Bcl-2 status were evaluated by immunohistochemistry in each case. Result: The study included 58 cases, with mean patient age of 47.07 years and male: female ratio of 1.89:1. Bcl-2 positivity was seen in 32.7% of the cases. Weak, moderate, and strong expression of Bcl-2 was seen in 12.1%, 12.1%, and 8.5% of cases respectively. Even though early stages of colorectal carcinoma showed greater frequency of Bcl-2 expression than advanced stages (36.3% versus 28%), however this association was not statistically significant. Conclusion: Lack of statistically significant correlation between Bcl-2 immuno-histochemical expression and prognostic parameters like tumor grade and stage, suggests that Bcl-2 immunoexpression may not be a significant prognostic marker in colorectal carcinoma.